The Relationship Between The Intake of High Saturated Fat Foods with Breast Cancer in Premenopause Women and the Review According to Islamic Perspective - Choirun Nisa, Asri; Kuntarti Heruyanto, Retno; Arsyad, Muhammad (Jurnal Indonesia Sosial Sains, 2023)
Cancer is one of the leading causes of death in the world. According to WHO, there are 2.3 million women diagnosed with breast cancer. Breast cancer appears more aggressive in premenopausal women. Unhealthy lifestyles such as excessive alcohol consumption, smoking, and eating high-fat foods can increase the risk of breast cancer. Allah SWT advised us to pay attention to our diet, because something excess is not good. Methods: The research is a quantitative research with observational analytic. The population is divided into a case group, 38 women who were diagnosed with breast cancer at the age of 35-47 years and a control group, namely 38 women who didn't suffer from breast cancer, aged 35-47 years. The sampling technique is non-probability sampling with the snowballing method. This research taken using a questionnaire containing identity and Semi-Quantitative FFQ and processed using SPSS, and analyzed using Chi-Square test. Results: A total of 45.8% of respondents aged 41-50 years when diagnosed with breast cancer with P-value (0.342). 71 respondents didn't have smoking habit with P-value (0.165), 75 respondents didn't have a habit of consuming alcohol with P-value (0.314), (73.9%) respondents from the case group had a family history of cancer with P-value (0.006). 55 respondents consumed foods high in saturated fat with a P-value (0.442). Conclusion: There was no significant association between age, alcohol consumption, smoking habits and consumption of saturated fat and the incidence of breast cancer, but there was a significant association between family history and the incidence of breast cancer.